Self-representation and the construction of the igbo world among igbo students in a public university in Nigeria (2015)
Construction of a distinctive cultural identity in a heterogeneous community entails employing cultural symbols to portray a group’s peculiarity. Within the university space in Nigeria, Igbo students re-enact the Igbo world through the employment of cultural symbols and ceremonials for the construction of an Igbo cultural identity. This study employs empirical evidence to explore how the Igbo world is re-enacted through ethnic identity construction within the territoriality of the university.1 By looking at how the local culture is translocalised in the university space, I explore the Igbo world in the context of this multi-ethnic, yet peculiar environment. The questions are: how do Igbo students in public universities in Nigeria (re)construct Igbo identity in the university space, using cultural forms, symbols, and ceremonials? In what forms do the conferred connect with the larger university community as a symbol of the “self” and the “collective,” reflecting group distinctiveness and contributing to the sustenance of the Igbo world in the university environment? This study has implications on the sustenance of Igbo cultural identity in a globalising world.